Radiological and pathological assessment with EOB-MRI after Y90 radiation lobectomy prior to liver resection for hepatocellular carcinoma. Issue 12 (December 2022) - Bekki, Yuki; Mahamid, Ahmad; Lewis, Sara; Ward, Stephen C.; Simpson, William; Argiriadi, Pamela; Kamath, Amita; Facciuto, Lucas; Patel, Rahul S.; Kim, Edward; Schiano, Thomas D.; Facciuto, Marcelo E.
Abstract: Background: Radiation lobectomy (RL) utilizes Yttrium-90 (Y90) radioembolization for achieving tumor control and inducing contralateral lobe hypertrophy. Our objective was to evaluate the chronological changes occurring radiologically and histopathologically after Y90 RL. Methods: We retrospectively reviewed 22 patients with chronic liver disease who underwent Y90 RL prior to planned liver resection for hepatocellular carcinoma. Gadolinium ethoxybenzyl diethylenetriamine penta-acetic acid (Gd–EOB-DTPA) enhanced magnetic resonance imaging (EOB-MRI) was performed every 3 months. Results: Future liver remnant volume (FLRV) significantly increased up to 9 months after Y90 RL. Gd–EOB-DTPA uptake in the treated lobe experienced a 40% reduction in enhancement ratio (ER) during ensuing first 3 months, and never recovered. The reduced ER in the non-tumoral parenchyma was significantly correlated with increased FLRV and FLR (r = 0.41 and r = 0.35, respectively; both p < 0.01). Histopathological evaluation of non-tumor liver tissue found features of sinusoidal obstruction syndrome as an early change after Y90 RL (median 5.7 months) and parenchymal collapse as a late change (mean 11 months). Discussion: The reduced uptake of Gd-EOB-DTPA at 3 months post Y90 RL correlates with a significant increase in FLRV prior to liver resection. EOB-MRI evaluation at 3 months can guide future plan of action after Y90 RL.